Teachers' Strategies in Implementing the Group Investigation Cooperative Model in Teaching Argumentative Text Writing at Junior High Schools - Lusia Oktri Wini; Rahmawati Rahmawati; Nurfadilah Nurfadilah (Journal of Education Language and Innovation, 2026)
Low critical thinking skills and minimal active student involvement are still the main challenges in learning to write argumentative texts in secondary schools. This study aims to describe the teacher's strategy for implementing the cooperative learning type, Group Investigation (GI), in argumentative writing instruction in Grade IX of junior high school, and to identify the teacher’s perspective on its impact on student engagement and activity. This research employed a descriptive qualitative approach with semi-structured interview techniques, involving a Bahasa Indonesia teacher as the research subject. Data were analyzed through stages of data reduction, data display, and conclusion drawing. The results reveal that the teacher implemented GI through stages such as forming heterogeneous groups, assigning roles, investigating topics, conducting group discussions, presenting, and writing individual argumentative texts. The teacher acted as an active facilitator, guiding and directing students, particularly in fostering inclusive, active discussions. GI proved effective not only in improving argumentative writing skills but also in fostering collaborative attitudes, responsibility, and student confidence in expressing opinions. Moreover, GI created a participatory and enjoyable learning atmosphere, positively influencing students’ motivation and self-confidence. These findings confirm that GI is an effective and relevant teaching strategy for developing students' critical thinking and communication skills in Bahasa Indonesia instruction.